Cyril Clemens collection - Clemens, Cyril, 1902-1999.
Correspondence, writings, clippings, photographs, and other papers relating chiefly to the International Mark Twain Society or to some aspect of Samuel Langhorne Clemens's life or literary works written by him under the name Mark Twain. Also includes production materials for several works on him by Cyril Clemens and copies of historical documents collected by Cyril Clemens. The 1686 document is a letter of James II, king of England.
In part, positive photocopies.
Biographer and editor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: International Mark Twain Society; James -- II, -- King of England, -- 1633-1701 -- Correspondence; Twain, Mark, -- 1835-1910.; American literature; American wit and humor; Biographers; Editors